Extension for the Emancipation of the Silent Majority - Akinbode, I. A. (Obafemi Awolowo University Press, 2013)
This inaugural address could not have come at a better time than now when the country's extension system is in a state of utter confusion if not.total collapse. Extension as an educational process and programme is usually on the priority list of programmes to be jettisoned anytime there is problem in the nation's economy. Extension programmes and staff are moved from one agency to another, oftentimes .to those with little or no understanding of what it is all about, nor appreciation of its principles and philosophy, and they' are replaced with 'crash' programmes which often crash before take-off. The consequence of this is that the country's peasants who still account for about 95 percent of Nigeria's agricultural output suffer. This then is the origin, of the title of my inaugural lecture, "Extension for the emancipation of the silent majority".